2005
DOI: 10.1111/j.1365-2729.2005.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hypermedia annotations for foreign language reading

Abstract: This study first explores intermediate-level English learners' preferences for hypermedia annotations while they are engaged in reading a hypermedia text. Second, it examines whether multimedia annotations facilitate reading comprehension in the second language. The participants were 44 adult learners of English as a foreign language studying English for Academic Purposes. Data were collected through a tracking tool, a reading comprehension test, a questionnaire, and interviews. Results indicate that learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 11 publications
2
45
3
4
Order By: Relevance
“…Therefore, the second null hypothesis stating that there is no significant difference in PET scores across the posttest between simplified and authentic groups of experimental groups is accepted. The result of the present study is in contrast to the previous studies (Sakar and Ercetin, 2005;Merlot, 2000) that claimed that authentic text can have more influence on reader's language proficiency.…”
Section: B Results Of Posttest For the Control And Experimental Groupscontrasting
confidence: 56%
“…Therefore, the second null hypothesis stating that there is no significant difference in PET scores across the posttest between simplified and authentic groups of experimental groups is accepted. The result of the present study is in contrast to the previous studies (Sakar and Ercetin, 2005;Merlot, 2000) that claimed that authentic text can have more influence on reader's language proficiency.…”
Section: B Results Of Posttest For the Control And Experimental Groupscontrasting
confidence: 56%
“…On the other hand, others indicated that the use of hypertext glosses might not directly affect or minimally influence L2 learners' vocabulary acquisition, even though reading with the help of a variety of hypertext glosses appears to have a positive impact on the L2 learners' perceptions, motivation and attitudes toward hyperlinked reading (Aust, Kelley & Roby, 1993;Gettys, Imhof, & Kautz, 2001;Levine, Bejarano, Carrell, & Vered, 2004;Lim, & Shen, 2006;Leutner, 1998, 2003;Sakar, & Ercetin, 2004).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Park and Kim's study (2011) added a socio-cultural lens to our understanding of online reading by arguing that dialogue is an important reading strategy because interacting with the object and the context is a human nature and that their research participants dialogued with themselves, with others, and with online resources throughout their whole reading processes. Some new reading strategies unique to online reading were identified as well, including hypermedia reading, the use of computer accessories, the use of annotations and navigation (Akyel & Ercetin, 2009;Huang, 2012;Huang et al, 2009;Park & Kim, 2011;Sakar & Ercetin, 2005). It is also indicated that online readers tend to transfer the reading strategies they already have from one medium to another (Akyel & Ercetin, 2009;Elshair, 2002;Foltz, 1993;Huang, 2012).…”
Section: Reading Strategies and Impact Factorsmentioning
confidence: 99%